2005
DOI: 10.1007/s11882-005-0091-z
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal asthma: underlying mechanisms and treatment

Abstract: Nocturnal asthma is defined by a drop in forced expiratory volume in 1 second (FEV(1)) of at least 15% between bedtime and awakening in patients with clinical and physiologic evidence of asthma. Nocturnal symptoms are a common part of the asthma clinical syndrome; up to 75% of asthmatics are awakened by asthma symptoms at least once per week, and approximately 40% experience nocturnal symptoms on a nightly basis. An extensive body of research has demonstrated that nocturnal symptoms such as cough and dyspnea a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 42 publications
1
19
0
1
Order By: Relevance
“…These results are consistent with our earlier work, which showed African ancestry to be inversely associated with measured FVC and FEV 1 (30) and with results showing nighttime lung function to be particularly decreased in individuals with nocturnal asthma relative to those without nocturnal symptoms (10). Although the causal mediation analysis demonstrated a marginally more significant result for FVC as compared with FEV 1 , both FVC and FEV 1 are highly correlated.…”
Section: Nocturnal Asthma Rates Between Africansupporting
confidence: 92%
See 1 more Smart Citation
“…These results are consistent with our earlier work, which showed African ancestry to be inversely associated with measured FVC and FEV 1 (30) and with results showing nighttime lung function to be particularly decreased in individuals with nocturnal asthma relative to those without nocturnal symptoms (10). Although the causal mediation analysis demonstrated a marginally more significant result for FVC as compared with FEV 1 , both FVC and FEV 1 are highly correlated.…”
Section: Nocturnal Asthma Rates Between Africansupporting
confidence: 92%
“…However, lung function studies have shown that affected individuals may demonstrate reduced FEV 1 both at night and throughout the day (10,11). The relative decrease appears to be greatest during the nighttime hours (12) and may be accompanied by increased eosinophil inflammation in the lung (13).…”
mentioning
confidence: 99%
“…114 Up to 75% of asthmatic subjects are awakened by breathing difficulties at least once a week, and approximately 40% experience nocturnal symptoms on a nightly basis. 115 Not all asthmatic patients experience a majority of their attacks at night, and allergists often distinguish patients with nocturnal asthma from those whose attacks do not consistently occur at night. However, up to 90% of asthmatic subjects experience nocturnal symptoms severe enough to awaken them from sleep.…”
Section: Sleep and Asthmamentioning
confidence: 99%
“…Although these nocturnal events are considered important in childhood asthma, their significance remains unclear due to a paucity of literature regarding this topic, in part due to the fact that most publications investigating nocturnal asthma have focused on adults (e.g., [2][3][4][5] ). Studies in children have examined the prevalence of nocturnal asthma [6][7][8][9][10][11] , associations with nocturnal asthma and sleep quality 10 and other factors associated with nocturnal asthma 9,[12][13][14][15] , but all of these studies were of short duration (≤7 days) or cross-sectional.…”
Section: Introductionmentioning
confidence: 99%